Ultraviolet and X-ray irradiance and flares from low-mass exoplanet host stars. Issue Volume 11:Issue S320(2015) (9th September 2016) - France, Kevin; Loyd, R. O. Parke; Brown, Alex
Abstract: The spectral and temporal behavior of exoplanet host stars is a critical input to models of the chemistry and evolution of planetary atmospheres. High-energy photons (X-ray to NUV) from these stars regulate the atmospheric temperature profiles and photochemistry on orbiting planets, influencing the production of potential "biomarker" gases. We report first results from the MUSCLES Treasury Survey, a study of time-resolved UV and X-ray spectroscopy of nearby M and K dwarf exoplanet host stars. This program uses contemporaneous Hubble Space Telescope and Chandra (or XMM) observations to characterize the time variability of the energetic radiation field incident on the habitable zones planetary systems at d ≲ 20 pc. We find that all exoplanet host stars observed to date exhibit significant levels of chromospheric and transition region UV emission. M dwarf exoplanet host stars display 30–7000% UV emission line amplitude variations on timescales of minutes-to-hours. The relative flare/quiescent UV flux amplitudes on weakly active planet-hosting M dwarfs are comparable to active flare stars (e.g., AD Leo), despite their weak optical activity indices (e.g., Ca II H and K equivalent widths). We also detect similar UV flare behavior on a subset of our K dwarf exoplanet host stars. We conclude that strong flares and stochastic variability are common, even on "optically inactive" M dwarfs hosting planetary systems. These results argue that the traditional assumption of weak UV fields and low flare rates on older low-mass stars needs to be revised.